COULD ASEAN COMMUNITY 2015 BE A FAIRNESS COMMUNITY FOR INDONESIAN ECONOMY? - Djarwono, Lukman Fahmi (PROCEEDING INTERNASIONAL SEMINAR, 2015)
âReady or not?â, a rhetorical question we met while discussing integration of Indonesia into ASEAN Economy Community 2015. All ASEAN member countries can trade each other without any barriers. Indonesia have not to be afraid and hesitate, because have enormously potential economy resources, including maritime sector, agriculture sector, micro and medium-scaled enterprises sector, and tourism sector, to join its community. Each countries have their own problems, and also each economy sectors have weaknesses that have to be assisted by government. Using concept of Fairness, we can analyze their own conditions, problems, and solutions. Administration of Joko Widodo have to protect them through subsidies policy. If Indonesia âunder new President Joko Widodoâ can utilize the ASEAN Economy Community 2015 as a moment to spread its market segment power, then Indonesia can take more advantages from the the regime.Keywords: Indonesia; Economy; ASEAN Community 2015; Fairness